Cleo: 2014 2014
DOI: 10.1364/cleo_qels.2014.ftu2k.8
|View full text |Cite
|
Sign up to set email alerts
|

Subwavelength multilayer dielectrics: ultrasensitive transmission and breakdown of effective-medium

Abstract: We show that a structure of alternating dielectric layers with deep subwavelength thicknesses exhibits novel transmission effects that depend on the order of the layers and on nanometer scale variations of the layer widths. OCIS codes: (260.2065) Effective medium theory; (260.6970) Total internal reflection (160.3918) Metamaterials;Homogenization in optics is the process of replacing a complex structure of subwavelength sized components with an "effective medium" with uniform properties. It is a fundamentally … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
13
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(16 citation statements)
references
References 5 publications
3
13
0
Order By: Relevance
“…Specifically, and following two main results in [35], we will introduce two quantities: (8) The first one, , is essentially the difference between the reflectance of the actual multilayer and its homogenized counterpart, since the structure with can be regarded as "quasi-homogenous"; we recall that all discrepancies , as defined in Equation 4, scale quadratically with the period of the structure [cf. Figure 1(c)], so is "400 times more homogenous" than .…”
Section: Semi-infinite Multilayer Structurementioning
confidence: 99%
See 3 more Smart Citations
“…Specifically, and following two main results in [35], we will introduce two quantities: (8) The first one, , is essentially the difference between the reflectance of the actual multilayer and its homogenized counterpart, since the structure with can be regarded as "quasi-homogenous"; we recall that all discrepancies , as defined in Equation 4, scale quadratically with the period of the structure [cf. Figure 1(c)], so is "400 times more homogenous" than .…”
Section: Semi-infinite Multilayer Structurementioning
confidence: 99%
“…Nevertheless, a recent theoretical paper by H.H. Sheinfux et al [35] demonstrates that this commonly believed assumption may fail in certain regimes. Namely, when the angle of incidence is close to the critical angle of the total internal reflection, the actual multilayer and its effective-medium counterpart can have significantly different transmission spectra despite the deeply subwavelength layer thicknesses (smaller than 1/50 of the wavelength).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, the possibility of using the effective medium theory with geometries as simple as a multilayer dielectric stack under the principal condition of homogenization applicability, namely that the layer thicknesses must be small compared with the wavelength of light that interacts with them, has hardly ever been questioned from the very introduction of the effective medium approximation (EMA) 12 . Hence, alldielectric subwavelength multilayers, in which no waves with extremely large wave vectors are supported, have been expected to unconditionally obey the EMA Recently, the theoretical paper by Sheinfux et al 14 showed that this commonly believed assumption may fail in certain regimes even for the deeply subwavelength layer thicknesses (smaller than 1/50 of the wavelength). Namely, when the angle of incidence is approaching the critical angle of the total internal reflection, the multilayer stack and its effectivemedium counterpart exhibit significantly different transmission.…”
Section: Introductionmentioning
confidence: 99%